ANALISIS BREAK EVEN POIN HARGA KELAPA SAWIT PADA PETANI MANDIRI DI KECAMATAN SERUYAN HILIR TIMUR - Bandrang, Tirsa Neyatri; Fatimah Azzahro, Qurrotul A’ A’yun; Ramdan, Mochamad (Jurnal Ilmiah Mahasiswa AGROINFO GALUH, 2024)
Break Even Point (BEP) analysis is an analysis used to study the relationship between fixed costs, variable costs, and revenue levels at various levels of production volume operations. This study aims to: 1) Analyze the income of oil palm farming in independent smallholders in East Seruyan Hilir Regency, 2) Analyze the Break Event Point of oil palm production in independent smallholders in East Seruyan Hilir Regency, 3) Analyze the Break Even Point of oil palm prices in independent smallholders in East Seruyan Hilir Regency. The research method used is the case study method, which is research conducted by looking directly at the field. The data used in the preparation of this study are primary data, secondary data and equipped with documentation. Where the primary data is in the form of respondents' answers to questions asked by the researcher to farmers using a questionnaire, while secondary data is obtained from installations related to the research. The sample in this study consisted of 6 villages with the number of respondents (samples) taken through the Accidental Sampling Technique which amounted to 91 respondents. The results of the study show that the income of oil palm farming in Seruyan Hilir Timur Regency for one year, the average annual net income is Rp 42,644,348. Then related to BEP (Break Even Point) oil palm agricultural production in East Seruyan Hilir Regency is categorized as detrimental with an average BEP production of 74072 kg, and BEP (Break Even Point) the price of oil palm agriculture in East Seruyan Hilir Regency is categorized as detrimental because the farmer's income per kg is Rp 2000/kg < the BEP price is Rp 15,277/kg from this statement the farmer's income exceeds the minimum income